Symptom Monitoring With Patient-Reported Outcomes During Routine Cancer Treatment: A Randomized Controlled Trial - Basch, Ethan; Deal, Allison M; Kris, Mark G; Scher, Howard I; Hudis, Clifford A; Sabbatini, Paul; Rogak, Lauren; Bennett, Antonia V; Dueck, Amylou C; Atkinson, Thomas M; Chou, Joanne F; Dulko, Dorothy; et al. (Journal of clinical oncology, 2016)
There is growing interest to enhance symptom monitoring during routine cancer care using patient-reported outcomes, but evidence of impact on clinical outcomes is limited. We randomly assigned patients receiving routine outpatient chemotherapy for advanced solid tumors at Memorial Sloan Kettering Cancer Center to report 12 common symptoms via tablet computers or to receive usual care consisting of symptom monitoring at the discretion of clinicians. Those with home computers received weekly e-mail prompts to report between visits. Treating physicians received symptom printouts at visits, and nurses received e-mail alerts when participants reported severe or worsening symptoms. The primary outcome was change in health-related quality of life (HRQL) at 6 months compared with baseline, measured by the EuroQol EQ-5D Index. Secondary endpoints included emergency room (ER) visits, hospitalizations, and survival. Among 766 patients allocated, HRQL improved among more participants in the intervention group than usual care (34% v 18%) and worsened among fewer (38% v 53%; P < .001). Overall, mean HRQL declined by less in the intervention group than usual care (1.4- v 7.1-point drop; P < .001). Patients receiving intervention were less frequently admitted to the ER (34% v 41%; P = .02) or hospitalized (45% v 49%; P = .08) and remained on chemotherapy longer (mean, 8.2 v 6.3 months; P = .002). Although 75% of the intervention group was alive at 1 year, 69% with usual care survived the year (P = .05), with differences also seen in quality-adjusted survival (mean of 8.7 v. 8.0 months; P = .004). Benefits were greater for participants lacking prior computer experience. Most patients receiving intervention (63%) reported severe symptoms during the study. Nurses frequently initiated clinical actions in response to e-mail alerts. Clinical benefits were associated with symptom self-reporting during cancer care.